2023
DOI: 10.3390/molecules28062492
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Equilibrium in Co-Amorphous Systems: Experiment and Prediction

Abstract: In this work, the solid–liquid equilibrium (SLE) of four binary systems combining two active pharmaceutical ingredients (APIs) capable of forming co-amorphous systems (CAMs) was investigated. The binary systems studied were naproxen-indomethacin, naproxen-ibuprofen, naproxen-probucol, and indomethacin-paracetamol. The SLE was experimentally determined by differential scanning calorimetry. The thermograms obtained revealed that all binary mixtures investigated form eutectic systems. Melting of the initial binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Soare et al 25 reported SLE data for the binary systems of ibuprofendrotaverine hydrochloride and ketoprofen-drotaverine hydrochloride. Zemańkováet al 26 experimentally determined the SLE of four binary systems, including naproxen-indomethacin, naproxen-ibuprofen, naproxen-probucol, and indomethacinparacetamol. In line with these studies, our research aims to contribute to this field by investigating new SLE data for the poorly water-soluble anticancer API, p-toluenesulfonamide.…”
Section: Introductionmentioning
confidence: 99%
“…Soare et al 25 reported SLE data for the binary systems of ibuprofendrotaverine hydrochloride and ketoprofen-drotaverine hydrochloride. Zemańkováet al 26 experimentally determined the SLE of four binary systems, including naproxen-indomethacin, naproxen-ibuprofen, naproxen-probucol, and indomethacinparacetamol. In line with these studies, our research aims to contribute to this field by investigating new SLE data for the poorly water-soluble anticancer API, p-toluenesulfonamide.…”
Section: Introductionmentioning
confidence: 99%